Mercury Monohalides as Ligands in Transition Metal Complexes - Matteo Busato; Jesús Castro; Domenico Piccolo; Marco Bortoluzzi (Molecules)
The main categories of transition metal–mercury heterometallic compounds are briefly summarized. The attention is focused on complexes and clusters where the Hg-Y fragment, where Y represents a halide atom, interacts with transition metals. Most of the structurally characterized derivatives are organometallic compounds where the transition metals belong to the Groups 6, 8, 9 and 10. More than one Hg-Y group can be present in the same compound, interacting with the same or with different transition metals. The main synthetic strategies are discussed, and structural data of representative compounds are reported. According to the isolobality with hydrogen, Hg-Y can form from one to three M-Hg-Y bonds, but further interactions can be present, such as mercurophilic and Hg···halide contacts. The formal oxidation state of mercury is sometimes ambiguous and thus Hg-Y can be considered as a Lewis acid or base on varying the transition metal fragment. Density functional theory calculations on selected Group 6 and Group 9 model compounds are provided in order to shed light on this aspect.